1998
DOI: 10.1139/y98-048
|View full text |Cite
|
Sign up to set email alerts
|

Immune responses to inflammation and trauma: a physical training model

Abstract: Physical activity and training have some potential as tools for examining immune responses to inflammation and trauma. Contributors to the present symposium review various aspects of the inflammatory process, including issues of lymphocyte recirculation and endotoxemia. They examine also the extent and nature of the immune disturbances induced by acute and chronic exercise and consider parallels between such responses and cellular manifestations of clinical sepsis. Factors modulating immune responses during ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 20 publications
0
5
0
2
Order By: Relevance
“…It has been shown that frequent bouts of PE with exposure to harsh environments such as extremes of heat, cold and humidity, as well as pathogens and stressors to the immune system including lack of sleep, severe mental stress, malnutrition, and bodyweight loss can precipitate diseases associated with inflammatory conditions (Neiman and Pedersen, 1999), which in many respects mimics the immune reactions observed in clinical sepsis (Shephard and Shek, 1998). This indicates that exhaustive exercise or acute bouts of exercise in adverse environmental conditions may act as a deterrent to the normal functioning of the immune system, inducing immunosuppression and increased susceptibility to infections.…”
Section: Environmental Enrichmentmentioning
confidence: 99%
“…It has been shown that frequent bouts of PE with exposure to harsh environments such as extremes of heat, cold and humidity, as well as pathogens and stressors to the immune system including lack of sleep, severe mental stress, malnutrition, and bodyweight loss can precipitate diseases associated with inflammatory conditions (Neiman and Pedersen, 1999), which in many respects mimics the immune reactions observed in clinical sepsis (Shephard and Shek, 1998). This indicates that exhaustive exercise or acute bouts of exercise in adverse environmental conditions may act as a deterrent to the normal functioning of the immune system, inducing immunosuppression and increased susceptibility to infections.…”
Section: Environmental Enrichmentmentioning
confidence: 99%
“…11,12 Pada penelitian ini dilakukan pengukuran tekanan dan compliance telinga tengah, serta menentukan tipe kurva timpanogram dengan timpanometri sebelum dan selama PNG terpasang, untuk mengetahui tingkat kejadian otitis media efusi. Hasil pengukuran timpanometri tersebut dikelompokkan berdasarkan kriteria Jerger sebagai berikut: 13,14 Tipe A: kurva timpanogram menunjukkan puncak compliance yang jelas berada pada tekanan ±50 daPa untuk dewasa, sedangkan pada anak masih dapat dianggap normal hingga tekanan -150 daPa. Tipe Ad: merupakan timpanogram tipe A tetapi dengan kurva sangat tinggi.…”
Section: Pendahuluanunclassified
“…19 Timpanogram tipe B merepresentasikan adanya cairan di telinga tengah. [13][14][15] Dari 34 subjek yang dilakukan pemeriksaan timpanometri hanya satu subjek yang terekam timpanogram tipe B (Tabel 5). Keadaan ini terjadi pada hari ke-2 dan ke-3 setelah pemasangan PNG dengan subjek pascaoperasi laringektomi dan PNG terpasang selama 7 hari.…”
Section: Pembahasanunclassified
“…2 3 In general, the literature suggests that acute exercisefor example, marathon and ultramarathon runningresults in an associated reduction in aspects of immune competence so that such athletes may be at increased risk of illness and need to pay particular attention to their nutritional state, hygiene, and exposure to infections. 3 It has been suggested that exercise induced reductions in particular lymphocyte subsets in runners is more dependent on training intensity than volume and is transient. 4 Other researchers consider that immunosuppression caused by stress as a result of acute exercise is not due to reallocation of scarce metabolic components but may represent a mechanism to reduce the potential of an autoimmune response.…”
mentioning
confidence: 99%